Photo-thermal catalyst as well as preparation method and application thereof
The carbon dot activation of CO2 and epoxides by synthesizing carbon dots by gallic acid and polyethyleneimine is realized, and the preparation of photothermal catalysts is solved, which is complicated, high cost and high reaction energy consumption in the prior art, and the high efficiency, green and low energy consumption preparation of cyclic carbonates is realized.
Patent Information
- Application Number
- CN202411115922.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-14
- Publication Date
- 2025-04-18
AI Technical Summary
In the prior art, the catalyst for catalyzing the synthesis of cyclic carbonate with CO2 and epoxide is complex in preparation, high in cost, and has a large reaction energy consumption. The carbon dot catalyst can only activate epoxy molecules, has no ability to activate CO2, and requires a cocatalyst, and the reaction requires an external heating source, which increases energy consumption.
The carbon dots synthesized by gallic acid and polyethyleneimine use hydroxyl groups, carboxylic acids and amino functional groups on their surface to activate the epoxide, and the CO2 is activated by highly graphitized carbon to achieve photothermal conversion without metals, cocatalysts, additives and solvents.
The cycloaddition reaction between CO2 and epoxy molecules catalyzed by carbon dots under metal-free, promoter-free, additive-free and solvent-free conditions is achieved, which improves the yield and catalytic efficiency of cyclic carbonate, and the reaction is green, low-energy consumption and low-cost.
Smart Images

Figure BDA0004993612970000043 
Figure BDA0004993612970000051 
Figure BDA0004993612970000052
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of organic synthesis, and in particular to a photothermal catalyst and a preparation method and application thereof. Background Art
[0002] Cyclic carbonate is an organic compound with many useful properties, which is widely used in the fields of high boiling point polar solvents, battery electrolytes, polymer material precursors, fuel additives, plastics and synthetic intermediates. A major way to produce cyclic carbonate in industry is the cycloaddition reaction of CO2 with epoxides. Due to the chemical inertness of CO2, such reactions usually need to be carried out under high temperature and high pressure conditions, and require the participation of catalysts. In order to avoid harsh reaction conditions such as high temperature and high pressure, and to improve the conversion rate of CO2 with epoxide reactions, some efficient catalysts such as homogeneous catalysts (Schiff bases, ionic liquids, metal complexes) and heterogeneous catalysts (covalent organic frameworks, metal organic frameworks, mesoporous oxides, porous polymers) have been developed. However, the preparation steps of these catalysts are complicated, all of which require the use of strong Lewis acidic metal complexes and environmentally harmful halogen ions, and need to be catalyzed under heating.
[0003] In recent years, carbon dots, as a new type of environmentally friendly and easy-to-produce carbon nanomaterial, can realize photoelectron transfer and photothermal conversion, making it a potential photothermal catalyst ( Figure 1 ). However, the carbon dot-based photothermal catalysts reported so far need to be combined with conjugated organic framework molecules or with metal materials to show good photothermal catalytic activity. There are few reports on the use of unmodified or composite carbon dots as single photothermal catalysts. At the same time, in the known reports of using carbon dots as catalysts to catalyze the cycloaddition of CO2 and epoxides to prepare cyclic carbonates, carbon dots can only activate epoxide molecules and have no activation ability for CO2, so the use of co-catalysts is required. In addition, this type of reaction catalyzed by carbon dots still requires heating from an external heat source, which increases energy consumption and is not conducive to the green and low-energy preparation of cyclic carbonates.
[0004] Therefore, the art urgently needs a carbon dot catalyst that is easy to prepare and inexpensive, has high catalytic activity and can simultaneously activate CO2 and epoxy molecules, has efficient photothermal conversion capabilities, and efficiently utilizes solar energy for the preparation of cyclic carbonates. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a photothermal catalyst and a preparation method and application thereof.
[0006] In a first aspect, the present invention provides a photothermal catalyst comprising carbon dots prepared by gallic acid and polyethyleneimine.
[0007] In some embodiments, the surface of the carbon dots includes hydroxyl, carboxylic acid and amino functional groups, and the carbon core of the carbon dots includes pyridinic nitrogen and graphitic nitrogen groups.
[0008] In some embodiments, the photothermal conversion efficiency of the carbon dots is above 40%, preferably 45-60%.
[0009] The carbon dots synthesized by gallic acid and polyethyleneimine in the present invention have excellent light-to-heat conversion efficiency and can convert solar energy into heat required for the reaction. At the same time, the hydroxyl, carboxylic acid and amino groups on the surface of the carbon dots are conducive to activating epoxides through hydrogen bond interactions. The polar groups (hydroxyl and carboxylic acid) on the surface of the carbon dots and the highly graphitized carbon cores are used to activate the epoxy molecules and carbon dioxide, respectively.
[0010] In some embodiments, the carbon dots have G / I D Greater than 1.
[0011] In some embodiments, the carbon dots have G / I D The carbon dots of the present invention have a high degree of graphitization.
[0012] In some embodiments, the average particle size of the carbon dots is 2-3 nm, for example, 2.1 nm, 2.2 nm, 2.3 nm, 2.4 nm, 2.5 nm, 2.6 nm, 2.7 nm, 2.8 nm, 2.9 nm, 3 nm or any value therebetween.
[0013] In some embodiments, the average particle size of the carbon dots is 2.1-2.5 nm.
[0014] In some embodiments, the carbon dots are spherical in shape.
[0015] In some embodiments, the carbon dots are at 0.1 W / cm 2 Under the irradiation of a high-intensity xenon lamp, the temperature can be raised to 60°C in 1 minute.
[0016] In some embodiments, the carbon dots are at 0.3 W / cm 2 Under the irradiation of a high-intensity xenon lamp, the temperature can be raised to 120°C in 1 minute.
[0017] In some embodiments, the carbon dots are at 0.5 W / cm 2 Under the irradiation of a high-intensity xenon lamp, the temperature can be raised to 140°C in 1 minute.
[0018] In some embodiments, the carbon dots are at 0.7 W / cm 2Under high-intensity xenon lamp irradiation, the temperature can be raised to 175°C in 1 minute.
[0019] In some embodiments, the carbon dots are at 0.9 W / cm 2 The temperature can be raised to 200°C in 1 minute under high-intensity xenon lamp irradiation.
[0020] In some embodiments, the benzyl glycidyl ether containing 5 wt % of the carbon dots is heated to 0.7 W / cm 2 The temperature can be raised to 100°C in 15 minutes under high-intensity xenon lamp irradiation.
[0021] In a second aspect, the present invention provides a method for preparing the photothermal catalyst described in the first aspect of the present invention, comprising the following steps: mixing gallic acid and polyethyleneimine and performing hydrothermal carbonization, filtering, and dialyzing the filtrate.
[0022] In some embodiments, the molar ratio of the gallic acid to the polyethyleneimine is 10:0.1-0.1:10, for example, 0.5:1, 0.6:1, 0.8:1, 1:1, 1.2:1, 1.5:1, 5:1, 10:1, 15:1, 20:1, 30:1 or any value therebetween.
[0023] In some embodiments, the temperature of the hydrothermal carbonization is 100-200°C; for example, 100°C, 120°C, 140°C, 160°C, 180°C, 200°C or any value therebetween.
[0024] In some embodiments, the hydrothermal carbonization time is 5-12 h, for example, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h or any value therebetween.
[0025] In some embodiments, the hydrothermal carbonization is performed in a high temperature oven.
[0026] In some embodiments, the solvent used in the mixing is ultrapure water.
[0027] In some embodiments, the molecular weight cutoff of the dialysis is 800-1200 Da, such as 800 Da, 900 Da, 1000 Da, 1100 Da, 1200 Da or any value therebetween.
[0028] In some embodiments, the filtering uses a filter.
[0029] In some embodiments, the filter has a specification of 0.2-0.25 μm, such as 0.2 μm, 0.21 μm, 0.22 μm, 0.23 μm, 0.24 μm, 0.25 μm or any value therebetween.
[0030] In some embodiments, the temperature is cooled to 20-40°C after hydrothermal carbonization, such as 20°C, 25°C, 30°C, 35°C, 40°C or any value therebetween.
[0031] In some embodiments, dialysis is performed using a dialysis bag.
[0032] In some embodiments, the dialysis duration is 1-5 days, such as 1 day, 2 days, 3 days, 4 days, 5 days or any value therebetween.
[0033] In some embodiments, drying is performed after dialysis is completed.
[0034] In some embodiments, drying can be performed by freeze drying or oven drying.
[0035] In some embodiments, the oven drying temperature is 100-150°C, for example, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C or any value therebetween.
[0036] In a third aspect, the present invention provides a use of the photothermal catalyst described in the first aspect of the present invention or the photothermal catalyst obtained by the preparation method described in the second aspect of the present invention in a cycloaddition reaction.
[0037] In some embodiments, the cycloaddition reaction is a reaction of carbon dioxide with an epoxy compound to prepare a cyclic carbonate; the epoxy compound has one or more
[0038] In a fourth aspect, the present invention provides a method for preparing a cyclic carbonate, comprising: under the conditions of light and the presence of the photothermal catalyst described in the first aspect of the present invention or the photothermal catalyst obtained by the preparation method described in the second aspect of the present invention, a cycloaddition reaction is carried out on an epoxide and carbon dioxide to generate the cyclic carbonate; the epoxide has one or more
[0039] The present invention realizes the cycloaddition reaction of CO2 and epoxy molecules catalyzed by carbon dots under light conditions without metal, co-catalyst, additive or solvent, and obtains a series of useful cyclocarbonate compounds in a green and low-energy manner.
[0040] The present invention utilizes a photothermal catalyst to prepare cyclic carbonates, and the method is simple, low in cost, high in photothermal catalytic efficiency, high in cyclic carbonate yield, green in reaction, and has wide substrate universality.
[0041] In some embodiments, the epoxy compound is selected from the structure shown in Formula I, and the cyclic carbonate is selected from the structure shown in Formula II:
[0042]
[0043]
[0044] R1 has a structure represented by -L-F1, and R2 and R3 have a structure represented by -L-F2-;
[0045] Wherein, L is selected from a single bond, a C1-C5 alkylene group, -O- and a combination thereof; L is connected to an epoxy compound or a cyclic carbonate;
[0046] F1 is selected from substituted or unsubstituted C3-C15 alkenyl, substituted or unsubstituted C3-C15 alkynyl, substituted or unsubstituted C6-C30 aryl, substituted or unsubstituted C3-C24 heteroaryl;
[0047] F2 is selected from C1-C30 alkylene, preferably substituted or unsubstituted C1-C10 alkylene, substituted or unsubstituted C6-C30 arylene, substituted or unsubstituted C3-C24 heteroaryl and combinations thereof;
[0048] The substituted substituent is selected from halogen, C1-C5 alkyl, C1-C5 alkoxy, cyano, and nitro.
[0049] In some embodiments, F1 is selected from substituted or unsubstituted C3-C8 alkenyl, substituted or unsubstituted C3-C8 alkynyl, substituted or unsubstituted C6-C12 aryl, substituted or unsubstituted C3-C10 heteroaryl.
[0050] In some embodiments, F1 is selected from substituted or unsubstituted C3-C5 alkenyl, substituted or unsubstituted C3-C5 alkynyl, substituted or unsubstituted phenyl, substituted or unsubstituted furanyl, substituted or unsubstituted thienyl, substituted or unsubstituted pyrrolyl.
[0051] In some embodiments, F2 is selected from C1-C8 alkylene, C6-C12 arylene, C3-C10 heteroaryl, and combinations thereof.
[0052] In some embodiments, F2 is selected from substituted or unsubstituted C1-C5 alkylene, substituted or unsubstituted phenylene, substituted or unsubstituted furanyl, substituted or unsubstituted thienyl, substituted or unsubstituted pyrrolyl, and combinations thereof.
[0053] In some embodiments, the substituted substituent is selected from F, Cl, Br, I, methyl, ethyl, propyl, isopropyl, butyl, pentyl, methoxy, ethoxy, cyano, and nitro.
[0054] In some embodiments, the epoxy compound is selected from one or more of the following compounds:
[0055]
[0056]
[0057] In some embodiments, the light irradiation is sunlight irradiation and / or xenon lamp irradiation.
[0058] In some embodiments, the illumination can focus sunlight using a Fresnel lens to illuminate the reaction under the sunlight.
[0059] In some embodiments, the intensity of the light is 0.3-1 W / cm 2 , for example 0.3W / cm 2 , 0.4W / cm 2 , 0.5W / cm 2 、0.6W / cm 2 , 0.7W / cm 2 , 0.8W / cm 2 , 0.9W / cm 2 , 1W / cm 2 or any value in between.
[0060] In some embodiments, based on the mass of the photothermal catalyst and the epoxy compound, the amount of the photothermal catalyst is 1-10wt%, for example, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt% or any value therebetween.
[0061] Compared with the prior art, the present invention has the following excellent effects:
[0062] (1) The present invention utilizes a photothermal catalyst to prepare cyclic carbonates, which has the advantages of simple method, low cost, high photothermal catalytic efficiency, high yield of cyclic carbonates, green reaction, and wide substrate universality, thus overcoming the defects of the prior art in catalyzing the synthesis of cyclic carbonates from CO2 and epoxy molecules, such as complex preparation, high cost, and high reaction energy consumption.
[0063] (2) Under light conditions, the present invention realizes the cycloaddition reaction of CO2 and epoxy molecules catalyzed by a photothermal catalyst under metal-free, co-catalyst-free, additive-free and solvent-free conditions, and obtains a series of useful cyclocarbonate compounds in a green and low-energy manner. BRIEF DESCRIPTION OF THE DRAWINGS
[0064] Figure 1 It is a photothermal catalyst in the prior art;
[0065] Figure 2 TEM image of carbon dots in Example 1 of the present invention;
[0066] Figure 3This is a Raman spectrum of the carbon dots in Example 1 of the present invention;
[0067] Figure 4 This is the infrared spectrum of the carbon dots in Example 1 of the present invention;
[0068] Figure 5 This is the XPS graph of the carbon dots in Example 1 of the present invention;
[0069] Figure 6 is the absorption spectrum of the carbon dots in Example 1 of the present invention;
[0070] Figure 7 This is a solid photothermal effect diagram of carbon dots in Example 1 of the present invention;
[0071] Figure 8 This is a photothermal effect diagram of carbon dots in benzyl glycidyl ether in Example 1 of the present invention;
[0072] Fig. 9 This is a cycle performance diagram of the carbon dots in Example 1 of the present invention;
[0073] Fig.10 The high performance liquid chromatography (HPLC) spectrum of (S)-7 of compound 7 of the present invention, (a) is the racemic spectrum, and (b) is the spectrum of (S)-7. DETAILED DESCRIPTION
[0074] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments and drawings. The specific embodiments described herein are only used to explain the present invention and are not intended to constitute any limitation to the present invention.
[0075] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0076] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used in the following examples, etc., can all be purchased on the market or can be obtained by existing methods; the reagent amounts, unless otherwise specified, are the reagent amounts used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods.
[0077] Example 1
[0078] Gallic acid and polyethyleneimine were dissolved in ultrapure water at a molar ratio of 1:1 and mixed evenly to obtain a mixed solution. The mixed solution was transferred to a reactor and placed in a high-temperature oven for hydrothermal carbonization at a temperature of 180°C for 8 hours, and then naturally cooled to room temperature to obtain a reaction solution. The reaction solution was centrifuged and filtered with a 0.22 μm filter, and the filtrate was dialyzed with a 1000 Da dialysis bag for 3 days and freeze-dried to obtain carbon dots CDs.
[0079] Transmission electron microscopy (TEM) images of carbon dots are shown in Figure 2 As shown. Figure 2 It can be seen that the average particle size of carbon dots is 2.3±0.2nm, the shape is spherical, and the lattice spacing is 0.21nm, which belongs to the (100) lattice stripes of graphene. The Raman spectrum of carbon dots is shown in Figure 3 As shown. Figure 3 It can be seen that at 1323cm -1 and 1523cm -1 The peaks correspond to the disordered carbon material (D band) and graphite (G band) of carbon dots. According to calculations, the I G / I D =1.37, indicating a high degree of graphitization, which is beneficial to the improvement of photothermal conversion efficiency. Figure 4 As shown, it can be seen that the carbon dots are at 3110-3631cm -1 There is an enhanced absorption band at 1658cm, which belongs to the stretching vibration of NH and OH groups. -1 and 1578cm -1 The peaks at 1450 cm-1 belong to C=O / C=N stretching vibration and NH bending vibration. -1 、1348cm -1 and 1125cm -1 The peaks belong to the stretching vibration of aromatic CN, CO and alkyl CN respectively. It can be seen that carbon dots contain abundant functional groups such as hydroxyl, amino, carbonyl, and imine. The X-ray photoelectron spectroscopy (XPS) of carbon dots is shown in Figure 2. Figure 5 As shown. It can be seen that carbon dots contain carbon, nitrogen, oxygen, and hydrogen elements. Among them, in terms of atomic percentage (number of atoms), carbon accounts for 70.34%, nitrogen content is relatively high, accounting for 14.15%, and oxygen accounts for 15.51%. The absorption spectrum of carbon dots is shown in Figure 6 As shown in the figure, carbon dots have strong absorption in the wavelength range of 300-1200nm, indicating that they have a good absorption range for sunlight. Take 41mg of carbon dots and expose them to light with an intensity of 0.1W / cm 2 , 0.3W / cm 2 , 0.5W / cm 2 , 0.7W / cm 2 , 0.9W / cm2 The carbon dots were irradiated with light, and then the temperature change was tested with an infrared thermometer to obtain the solid photothermal effect of the carbon dots. Figure 7 As shown, it can be seen that the carbon dots have a very strong photothermal conversion efficiency. Through calculation, the photothermal conversion efficiency can reach 54%.
[0080] Example 2
[0081] Different from Example 1, gallic acid and polyethyleneimine are added in a molar ratio of 4:1 to obtain 4-CDs.
[0082] Example 3
[0083] Different from Example 1, gallic acid and polyethyleneimine are added in a molar ratio of 2:1 to obtain 2-CDs.
[0084] Example 4
[0085] Different from Example 1, gallic acid and polyethyleneimine were added in a molar ratio of 1:2 to obtain 0.5-CDs.
[0086] Application Example 1 Reaction Condition Screening
[0087] (1) Lighting condition screening
[0088] At 0.1, 0.3, 0.5, 0.7 and 0.9 W / cm 2 5 wt % CDs (41 mg) and 5 mmol of epoxy compound (benzyl glycidyl ether, 0.8 mL) were mixed and irradiated under simulated sunlight. Figure 8 shown.
[0089] In 20 minutes, the temperature changed from the initial 26°C to 43, 61, 71, 94 and 104°C, respectively. Considering that the reaction of CO2 with epoxide in the catalytic system is usually suitable for the temperature range of 80-120°C, the 0.7W / cm 2 A high intensity xenon lamp is used as the light source. Figure 8 It can be seen that carbon dots have good heating properties in epoxy molecules, which is conducive to the reaction.
[0090] (2) Catalyst screening
[0091] Cyclic carbonate is prepared in a solvent-free system using an epoxy compound (benzyl glycidyl ether) and CO2 as raw materials. The reaction formula is as follows:
[0092]
[0093] The specific reaction steps include: under light conditions, reacting an epoxy compound (i.e., benzyl glycidyl ether, 5 mmol, 0.8 mL) and CO2 (1 bar) under the catalysis of a catalyst. The reaction conditions and the temperature and yield reached after the reaction are shown in Table 1.
[0094] Experiments 1-10 at 0.7 W / cm 2 A high intensity xenon lamp (500W) was used as the light source.
[0095] In Experiment 1, the catalyst is the carbon dots CDs prepared in Example 1, and the amount used is 41 mg (5 wt %).
[0096] In Experiment 2, the catalyst is carbon dots U-CDs prepared from gallic acid and urea, and the amount used is 41 mg (5 wt %).
[0097] The preparation method of U-CDs includes: dissolving gallic acid and urea in ultrapure water at a molar ratio of 1:1, uniformly mixing, and obtaining a mixed solution. The mixed solution is transferred into a reaction kettle and placed in a high-temperature oven for hydrothermal carbonization at a temperature of 180°C for 8 hours, and then naturally cooled to room temperature to obtain a reaction solution. The reaction solution is centrifuged and filtered with a 0.22 μm filter, and the filtrate is dialyzed with a 1000Da dialysis bag for 3 days, and freeze-dried to obtain carbon dot U-CDs.
[0098] In Experiment 3, the catalyst was the carbon dots 4-CDs prepared in Example 2, and the amount used was 41 mg (5 wt%).
[0099] The catalyst in Experiment 4 is the carbon dots 2-CDs prepared in Example 3, and the amount used is 41 mg (5 wt%).
[0100] The catalyst in Experiment 5 was the carbon dots 0.5-CDs prepared in Example 4, and the amount used was 41 mg (5 wt%).
[0101] The catalyst in Experiment 6 was the carbon dots CDs prepared in Example 1, with an amount of 20.51 mg (2.5 wt%).
[0102] In Experiment 7, the catalyst was carbon dots GA-CDs prepared from gallic acid, and the dosage was 41 mg (5 wt%).
[0103] The preparation method of GA-CDs includes: dissolving gallic acid in ultrapure water, uniformly mixing, and obtaining a gallic acid solution. The gallic acid solution is transferred into a reaction kettle and placed in a high-temperature oven for hydrothermal carbonization, the hydrothermal carbonization temperature is 180°C, the hydrothermal carbonization time is 8 hours, and then naturally cooled to room temperature to obtain a reaction solution. The reaction solution is centrifuged and filtered with a 0.22 μm filter, and the filtrate is dialyzed with a 1000Da dialysis bag for 3 days, and freeze-dried to obtain carbon dot GA-CDs.
[0104] In Experiment 8, the catalyst was carbon dots PEI-CDs prepared from polyethyleneimine, and the amount used was 41 mg (5 wt%).
[0105] The preparation method of PEI-CDs includes: dissolving polyethyleneimine in ultrapure water, uniformly mixing, and obtaining a polyethyleneimine solution. The polyethyleneimine solution is transferred into a reaction kettle and placed in a high-temperature oven for hydrothermal carbonization, the hydrothermal carbonization temperature is 180°C, the hydrothermal carbonization time is 8 hours, and then naturally cooled to room temperature to obtain a reaction solution. The reaction solution is centrifuged and filtered with a 0.22μm filter, and the filtrate is dialyzed with a 1000Da dialysis bag for 3 days, and freeze-dried to obtain carbon dot PEI-CDs.
[0106] The catalyst in Experiment 9 was polyethyleneimine PEI, and the amount used was 41 mg (5 wt%).
[0107] The catalyst in Experiment 10 was gallic acid GA, and the dosage was 41 mg (5 wt %).
[0108] The catalyst in Experiment 11 was polyethyleneimine and gallic acid in a molar ratio of 1:1, and the mass of polyethyleneimine and gallic acid was 10 wt % of the total mass of the epoxy compound (benzyl glycidyl ether) and the catalyst.
[0109] In Experiment 12, the catalyst is the carbon dots CDs prepared in Example 1, and sunlight is used as the light source.
[0110] Table 1
[0111]
[0112] The percentage content in the amount of catalyst in Table 1 refers to the mass percentage of the catalyst based on the mass of the photothermal catalyst and the epoxy compound (benzyl glycidyl ether). The reaction temperature refers to the temperature that the reaction system can reach after light irradiation.
[0113] Different catalysts have different photothermal effects, and the temperature reached by the reaction system after illumination is different, resulting in different catalytic yields.
[0114] As shown in Table 1, different catalysts have different heating capabilities for the reaction system under the same illumination conditions due to their different photothermal conversion capabilities. The more carbon dots there are, the stronger the heating effect on the system reaction liquid under illumination conditions. A reduction in the amount of carbon dots (such as Experiment 6) will lead to a worse heating effect of the reaction, and a reduction in the amount of carbon dots will lead to a reduction in catalytic sites and a decrease in catalytic yield.
[0115] As can be seen from Table 1, the catalysts composed of GA, PEI, GA / PEI and CDs synthesized with GA or PEI as single precursors all showed low photothermal conversion rates and poor catalytic reactivity.
[0116] Application Example 2: Reaction Substrate Expansion
[0117] The carbon dots in Example 1 were used as catalysts to catalyze the reaction of different epoxy compounds with CO2 to prepare cyclic carbonates. The specific reaction formula is as follows:
[0118]
[0119] The specific reaction steps include:
[0120] At 0.7W / cm 2 Under the irradiation of a strong xenon lamp, the epoxy compound (5 mmol) and CO2 (1 bar) were reacted in the presence of the catalyst (41 mg, 5 wt%) of Example 1. The specific products prepared and their yields are shown in Table 2.
[0121] Table 2
[0122]
[0123] As can be seen from Table 2, epoxides containing various functional groups can react successfully with CO2 under natural light to generate the corresponding cyclic carbonates within 24 hours with good yields and selectivity. For hindered epoxides containing aromatic ether groups, the yields of the cyclic carbonates of compounds 1-4 generated by the reaction are very high (87%-96%), as shown in Table 2. Active functional groups such as alkyl and olefins are also well tolerated during the photothermal catalytic process and provide the corresponding products 5 and 6 in high yields (93% and 89%, respectively). For the challenging low-reactivity and sterically bulky styrene oxide substrate, CDs also showed high catalytic reactivity, resulting in cyclic carbonate 7 with a yield of 70%. In addition, chiral styrene oxide can be smoothly converted to the corresponding chiral cyclic carbonate (S)-7 without any loss of chirality (>99% ee), indicating that selective ring opening occurs at the terminal position of the epoxide. The high-performance liquid chromatography (HPLC) spectrum of the chiral cyclic carbonate (S)-7 is shown in Figure 2. Fig.10 As shown, (a) is the racemic spectrum, and (b) is the spectrum of (S)-7. The functionalized diepoxide substrate is also suitable for CDs catalyst with a yield of 92%, and can be used as an important component for further synthesis of polymers such as polyurethane and polycarbonate.
[0124] The cyclic carbonate compounds are characterized as follows:
[0125]
[0126] The reaction was carried out according to the general operation steps, and the oily colorless liquid product was obtained by column chromatography separation (petroleum ether: ethyl acetate = 4:1). (905.7 mg, 87% yield). 1H NMR (500MHz, CDCl3) δ7.39-7.28(m,5H),4.84-4.77(m,1H),4.59(dd,J=12.0,25.5Hz,2H),4.47(t,J =8.5Hz,1H),4.37(dd,J=6.0,8.5Hz,1H),3.71(dd,J=4.0,11.0Hz,1H),3.61(dd,J=4.0,11.5Hz,1H). 13 C NMR (125MHz, CDCl3) δ154.89,137.02,128.49,127.99,127.67,74.95,73.59,68.76,66.20.
[0127]
[0128] The reaction was carried out according to the general operation steps, and a white solid product was obtained by column chromatography (petroleum ether: ethyl acetate = 4:1). (921.9 mg, 95% yield). 1 H NMR (500MHz, CDCl3) δ7.33-7.28(m,2H),7.03-6.99(m,1H),6.93-6.89(m,2H),5.04-4.99(m,1H),4.59( t,J=8.5Hz,1H),4.51(dd,J=5.5,8.5Hz,1H),4.23(dd,J=4.0,11.0Hz,1H),4.12(dd,J=3.5,10.5Hz,1H). 13 C NMR (125MHz, CDCl3) δ157.71,154.66,129.64,121.92,114.56,74.11,66.82,66.17.
[0129]
[0130] The reaction was carried out according to the general operation steps, and a white solid product was obtained by column chromatography (petroleum ether: ethyl acetate = 4:1). (997.6 mg, 96% yield). 1 H NMR (500MHz, CDCl3) δ7.18-7.14(m,2H),6.95-6.91(m,1H),6.80-6.76(m,1H),5.06-5.01(m,1H),4.61(t,J=8. 5Hz, 1H), 4.56 (dd, J=5.5, 8.5Hz, 1H), 4.24 (dd, J=3.0, 10.5Hz, 1H), 4.11 (dd, J=3.0, 11.0Hz, 1H), 2.22 (s, 3H). 13C NMR (125MHz, CDCl3) δ155.71,154.79,131.01,127.01,126.83,121.58,110.78,74.21,66.95,66.18,15.89.
[0131]
[0132] The reaction was carried out according to the general operation steps, and the product was obtained as a light yellow liquid by column chromatography (petroleum ether: ethyl acetate = 6:1). (900.7 mg, 91% yield). 1 H NMR(500MHz, CDCl3)δ7.42-7.39(m,1H),6.34(d,J=1.0Hz,2H),4.81-4.75(m,1H),4.56-4.46(m,2H),4.44 (t,J=8.5Hz,1H),4.31(dd,J=6.0,8.5Hz,1H),3.69(dd,J=4.0,11.0Hz,1H),3.61(dd,J=4.0,11.0Hz,1H). 13 C NMR (125MHz, CDCl3) δ154.83,150.61,143.07,110.33,110.02,74.85,68.41,66.16,65.18.
[0133]
[0134] The reaction was carried out according to the general operation steps, and column chromatography (petroleum ether: ethyl acetate = 6:1) was used to obtain a colorless liquid product (725.7 mg, 93% yield). 1 H NMR (500MHz, CDCl3) δ4.87-4.81(m,1H),4.50(t,J=8.5Hz,1H),4.38(dd,J=6.0,8.5Hz,1H),4.27 -4.15(m,2H),3.77(dd,J=4.0,11.0Hz,1H),3.71(dd,J=3.5,11.0Hz,1H),2.48(t,J=2.0Hz,1H). 13 CNMR (125MHz, CDCl3) δ154.79,78.46,75.54,74.67,68.35,66.10,58.72.
[0135]
[0136] The reaction was carried out according to the general operation steps, and column chromatography (petroleum ether: ethyl acetate = 6:1) was used to obtain a colorless liquid product (707.5 mg, 89% yield).1 H NMR (500MHz, CDCl3) δ5.89-5.80(m,1H),5.29-5.18(m,2H),4.84-4.78(m,1H),4.48(t,J=8.5Hz,1H),4. 37(dd,J=6.0,8.5Hz,1H),4.08-3.99(m,2H),3.68(dd,J=4.0,11.0Hz,1H),3.59(dd,J=3.5,11.0Hz,1H). 13 C NMR (125MHz, CDCl3) δ154.90,133.60,117.79,75.00,72.47,68.76,66.18.
[0137]
[0138] The reaction was carried out according to the general operation steps, and a white solid product was obtained by column chromatography (petroleum ether: ethyl acetate = 5:1). (576.1 mg, 70% yield). 1 H NMR (500MHz, CDCl3) δ7.47-7.40(m,3H),7.39-7.34(m,2H),5.68(t,J=8.0Hz,1H),4.80(t,J=8.0Hz,1H),4.34(t,J=8.0Hz,1H). 13 C NMR (125MHz, CDCl3) δ154.79,135.74,129.69,129.19,125.83,77.95,71.12.
[0139]
[0140] The reaction was carried out according to the general operation steps, and column chromatography (petroleum ether: ethyl acetate = 1:1) was used to obtain a colorless liquid product (1969.5 mg, 92% yield). 1 H NMR (500MHz, CDCl3) δ7.14(d,J=9.0Hz,4H),6.80(d,J=8.5Hz,4H),5.04-4.98(m,2H),4.60(t,J=8.5Hz,2 H), 4.52 (dd, J=6.0, 8.5Hz, 2H), 4.21 (dd, J=4.0, 10.5Hz, 2H), 4.12 (dd, J=3.5, 10.5Hz, 2H), 1.63 (s, 6H). 13C NMR (125MHz, CDCl3) δ155.62, 154.62, 144.32, 127.91, 114.02, 74.06, 66.88, 66.20, 41.81, 30.93.
[0141] Application Example 3
[0142] To explore the recyclability of CDs catalyst, the above-mentioned bicyclic carbonate 8 was synthesized with 1 atm CO2 as raw material under natural light conditions. After the catalyst was recycled 5 times, the yield slightly decreased from 92% to 84%, but it still had a high catalytic activity (such as Fig. 9 After 5 cycles of reaction, the loss rate of CDs was only 1.8 wt%, indicating that the system has excellent stability and recyclability.
[0143] Application Example 4
[0144] Cyclic carbonates were prepared in a solvent-free system using an epoxy compound (benzyl glycidyl ether, 1000 mmol) and CO2 as raw materials. Using the carbon dots in Example 1 as catalysts (8.63 g, 5 wt%), 176.98 g of cyclic carbonates were obtained with a yield of 85%. This demonstrates that the method of the present invention is simple, mild, and energy-saving, and has great potential for synthesizing cyclic carbonates from epoxides and CO2 on an industrial scale.
[0145] In summary, the present invention uses carbon dots CDs as photothermal catalysts for preparing cyclic carbonates. The carbon core of CDs generates heat energy and electrons under sunlight. The generated electrons and N sites activate the inert CO2. At the same time, the epoxide is effectively activated by the hydroxyl and carboxyl groups on the surface of CDs through hydrogen bonding. The active CO2 and epoxide react effectively at high temperatures induced by solar heat. CDs overcome the problems of previous photocatalysts and can effectively catalyze reactions without any co-catalysts under natural sunlight. It is suitable for 8 different cyclic carbonates prepared from different epoxides. As a photocatalyst, carbon dots CDs have the characteristics of low energy consumption and low cost, and are ideal catalysts for the industrial production of cyclic carbonates.
[0146] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A photothermal catalyst comprising carbon dots prepared by gallic acid and polyethyleneimine.
2. The photothermal catalyst according to claim 1, characterized in that: The carbon dot surface includes hydroxyl, carboxylic acid and amino functional groups, and the carbon core of the carbon dot includes pyridinic nitrogen and graphitic nitrogen groups; and / or The photothermal conversion efficiency of the carbon dots is above 40%, preferably 45-60%; and / or The I G / I D Greater than 1, preferably 1.1-1.
5.
3. The photothermal catalyst according to claim 1 or 2, characterized in that: The average particle size of the carbon dots is 2-3 nm, preferably 2.1-2.5 nm; and / or The carbon dots have a spherical shape; The carbon dots are at 0.1W / cm 2 Under the irradiation of high-intensity xenon lamp, the temperature can be raised to 60℃ in 1 minute; The carbon dots are at 0.3W / cm 2 Under the irradiation of high-intensity xenon lamp, the temperature can be raised to 120℃ in 1 minute; The carbon dots are at 0.5W / cm 2 Under the irradiation of high-intensity xenon lamp, the temperature can be raised to 140℃ in 1 minute; The carbon dots are at 0.7W / cm 2 Under the irradiation of high-intensity xenon lamp, the temperature can be raised to 175℃ in 1 minute; The carbon dots are at 0.9W / cm 2 Under the irradiation of high-intensity xenon lamp, the temperature can be raised to 200℃ in 1 minute; Benzyl glycidyl ether containing 5 wt% of the carbon dots at 0.7 W / cm 2 The temperature can be raised to 100°C in 15 minutes under high-intensity xenon lamp irradiation.
4. A method for preparing the photothermal catalyst according to any one of claims 1 to 3, comprising the following steps: mixing gallic acid and polyethyleneimine and performing hydrothermal carbonization, filtering, and dialyzing the filtrate; Preferably, the molar ratio of the gallic acid to the polyethyleneimine is 10:0.1-0.1:
10.
5. The preparation method according to claim 4, characterized in that: The temperature of the hydrothermal carbonization is 100-200°C; and / or The hydrothermal carbonization time is 5-12h.
6. The preparation method according to claim 4 or 5, characterized in that: The solvent used in the mixing is ultrapure water; and / or The molecular weight cut-off of the dialysis is 800-1200Da.
7. Use of the photothermal catalyst according to any one of claims 1 to 3 or the photothermal catalyst obtained by the preparation method according to any one of claims 4 to 6 in a cycloaddition reaction; Preferably, the cycloaddition reaction is a reaction of carbon dioxide and an epoxy compound to prepare a cyclocarbonate; The epoxy compound has one or more 8. A method for preparing a cyclic carbonate, comprising: Under the conditions of light and the presence of the photothermal catalyst according to any one of claims 1 to 3 or the photothermal catalyst obtained by the preparation method according to any one of claims 4 to 6, a cycloaddition reaction is carried out between the epoxy compound and carbon dioxide to generate the cyclocarbonate; The epoxy compound has one or more 9. The use according to claim 7 or the method according to claim 8, characterized in that: The epoxy compound is selected from the structure shown in Formula I, and the cyclic carbonate is selected from the structure shown in Formula II: R1 has a structure represented by -L-F1, and R2 and R3 have a structure represented by -L-F2-; Wherein, L is selected from a single bond, a C1-C5 alkylene group, -O- and a combination thereof; L is connected to an epoxy compound or a cyclic carbonate; F1 is selected from substituted or unsubstituted C3-C15 alkenyl, substituted or unsubstituted C3-C15 alkynyl, substituted or unsubstituted C6-C30 aryl, substituted or unsubstituted C3-C24 heteroaryl; F2 is selected from C1-C30 alkylene, preferably substituted or unsubstituted C1-C10 alkylene, substituted or unsubstituted C6-C30 arylene, substituted or unsubstituted C3-C24 heteroaryl and combinations thereof; The substituted substituent is selected from halogen, C1-C5 alkyl, C1-C5 alkoxy, cyano, and nitro; Preferably, F1 is selected from substituted or unsubstituted C3-C8 alkenyl, substituted or unsubstituted C3-C8 alkynyl, substituted or unsubstituted C6-C12 aryl, substituted or unsubstituted C3-C10 heteroaryl; Preferably, F1 is selected from substituted or unsubstituted C3-C5 alkenyl, substituted or unsubstituted C3-C5 alkynyl, substituted or unsubstituted phenyl, substituted or unsubstituted furanyl, substituted or unsubstituted thienyl, substituted or unsubstituted pyrrolyl; and / or F2 is selected from substituted or unsubstituted C1-C8 alkylene, C6-C12 arylene, C3-C10 heteroaryl and combinations thereof; Preferably, F2 is selected from substituted or unsubstituted C1-C5 alkylene, substituted or unsubstituted phenylene, substituted or unsubstituted furyl, substituted or unsubstituted thienyl, substituted or unsubstituted pyrrolyl, and combinations thereof; Preferably, the substituted substituent is selected from F, Cl, Br, I, methyl, ethyl, propyl, isopropyl, butyl, pentyl, methoxy, ethoxy, cyano, nitro; Preferably, the epoxy compound is selected from one or more of the following compounds:
10. The reaction according to claim 9, characterized in that The illumination is sunlight and / or xenon lamp illumination, and / or The intensity of light is 0.3-1W / cm 2 , and / or Based on the mass of the photothermal catalyst and the epoxy compound, the amount of the photothermal catalyst is 1-10wt%.